2021
DOI: 10.3389/frph.2021.732318
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic Androgenic Steroids Induce Reversible Left Ventricular Hypertrophy and Cardiac Dysfunction. Echocardiography Results of the HAARLEM Study

Abstract: Background: The use of anabolic androgenic steroids (AAS) is not uncommon among strength athletes. Several cross-sectional studies have linked AAS use to heart disease, but a causal role for AAS is not certain and it is unknown whether cardiac changes are reversible.Methods: Men of at least 18 years old intending to start an AAS cycle on short notice were included for comprehensive 3D echocardiographic examination before (T0), at the end of the cycle (T1), and 1 year after inclusion (T2) after a recovery perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
(26 reference statements)
0
17
0
1
Order By: Relevance
“…Alternatively, sub-microscopic effects might have changed the anatomy of the developing heart during the 2-day exposition. In adult strength athletes, a 6-week AAS cycle reversibly increased the left ventricle mass and reduced the ejection volume by 5% (Smit et al 2021 ). In view of the fact that the analysis of detailed cardiotoxic effects was beyond the scope of this study, we cannot unambiguously define the elevated heart beat rate in 10 µM MD treated individuals as anabolic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, sub-microscopic effects might have changed the anatomy of the developing heart during the 2-day exposition. In adult strength athletes, a 6-week AAS cycle reversibly increased the left ventricle mass and reduced the ejection volume by 5% (Smit et al 2021 ). In view of the fact that the analysis of detailed cardiotoxic effects was beyond the scope of this study, we cannot unambiguously define the elevated heart beat rate in 10 µM MD treated individuals as anabolic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Long-standing untreated hypertension might exacerbate the detrimental effects of AAS on cardiac structure and function, perhaps making blood pressure treatment in this population particularly relevant. The HAARLEM study, however, found no interaction between blood pressure and echocardiographic parametersprobably because the increase was mild and of relatively short duration (97). Future research is necessary to explore the efficacy of blood pressure-lowering medication in this group of patients as no trial to date has evaluated this.…”
Section: Hypertensionmentioning
confidence: 97%
“…Thirty-one men enrolled in the HAARLEM study were subjected to 3D echocardiography before, at the end, and a median of 8 months after the start of their self-administered AAS cycles (97). The prospective nature, comprehensive evaluation and long follow-up make the results of this trial particularly interesting.…”
Section: Cardiomyopathymentioning
confidence: 99%
“…Measurements took place before, during and twice after the cycle. Health effects were divided into several categories: positive and negative adverse effects reported by the subjects, the results of kidney and liver biochemistry in blood, and the outcome of psychological questionnaires [4 ▪ ]; the disruption and recovery of endogenous testosterone production and spermatogenesis [5 ▪ ]; the change of cardiovascular parameters during androgen abuse, such as blood pressure, lipid metabolism and erythrocytosis [6 ▪ ]; and change of cardiac structure and function as evaluated with 3D echocardiography [7].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…In the last 2−3 years several publications reported data from the HAARLEM study [3,4 ▪ –6 ▪ ,7], which is an acronym for health risks of anabolic androgenic steroid use by male amateur athletes. This cohort study takes precedence over much of the existing literature in this field due to its prospective design and relatively large size.…”
Section: Introductionmentioning
confidence: 99%